2008
DOI: 10.1007/s10344-008-0194-7
|View full text |Cite
|
Sign up to set email alerts
|

A half a century of measuring ungulate body condition using indices: is it time for a change?

Abstract: From a literature review of five wildlife ecology journals since 1937, we document how using indices to monitor ungulate body condition is common practice, with the kidney fat index (KFI = weight of fat around the kidneys/weight of kidneys without fat × 100) as the favoured tool (82% of studies). In this context, we highlight the problems of using indices when underlying statistical assumptions are not met (isometry, parallel slopes between treatments). We show, with real and simulated data for two cervids wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 20 publications
1
31
0
1
Order By: Relevance
“…However, it remains difficult to quantify the simple effect of spleen mass on macroparasite load without taking into account the confounding effects of body reserves and condition and their relationship with host nutrition (Coop and Kyriazakis 2001;Vicente et al 2007b;Serrano et al 2008). By correcting spleen mass for body mass (a reliable index of condition in roe deer, see Toïgo et al 2006), we observed significantly lower parasite loads in deer with relatively large spleens (for a given body size), suggesting that spleen size is indeed a reliable indicator of immunocompetence.…”
Section: Discussionmentioning
confidence: 81%
“…However, it remains difficult to quantify the simple effect of spleen mass on macroparasite load without taking into account the confounding effects of body reserves and condition and their relationship with host nutrition (Coop and Kyriazakis 2001;Vicente et al 2007b;Serrano et al 2008). By correcting spleen mass for body mass (a reliable index of condition in roe deer, see Toïgo et al 2006), we observed significantly lower parasite loads in deer with relatively large spleens (for a given body size), suggesting that spleen size is indeed a reliable indicator of immunocompetence.…”
Section: Discussionmentioning
confidence: 81%
“…We included the harvest date as a covariate for all analyses involving body mass. We added kidney mass as a covariate to models of kidney fat mass to correct for the effect of organ size on fat mass (Serrano et al ) and the hind foot length to models of peroneus mass to correct for the effect of body size.…”
Section: Methodsmentioning
confidence: 99%
“…Both KM and KF are positively correlated to nutritional status in Iberian wild goats (Serrano et al 2008b) and to body condition in a great range of mammals of different body sizes (from roe deer to moose, Serrano et al 2008a). As predicted, heavier goats (skeletally bigger and fatter) had more KM (R 2 =0.73, F 1,461 =1,281; p<0.01, linear relationship between body weight and KM) and KF (R 2 = 0.26, F 1,461 = 159.5; p < 0.01 following the same procedure) than lighter ones.…”
Section: Discussionmentioning
confidence: 98%
“…Changes in body condition-this term includes tissues necessary for a functionally normal life (defined as 'body reserves', according to Lindström and Piersma 1993) and those accumulated in anticipation of periods of shortage (defined as 'body stores', according to King and Murphy 1985)-have been related to several life-history traits in several ungulate species (Serrano et al 2008a). Commonly, this group of mammals allocates large amounts of energy to each breeding attempt (Pélabon et al 1995) and exhibits a wide range of resource-use tactics within the income-capital breeder continuum (Jönsson 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation